Activation of myeloid dendritic cells, effector cells and regulatory T cells in lichen planus. Issue 1 (December 2016) - Domingues, Rosana; Carvalho, Gabriel; Aoki, Valéria; Duarte, Alberto; Sato, Maria
Abstract Background Lichen planus (LP) is a chronic mucocutaneous inflammatory disease. Evaluating the balance between regulatory T cells and effector T cells could be useful for monitoring the proinflammatory profile of LP. Therefore, this study aimed to assess populations of dendritic cells (DCs) and regulatory and effector T cells in peripheral blood samples collected from patients with LP to evaluate the polyfunctionality of T cells upon toll-like receptor (TLR) activation. Methods Peripheral blood mononuclear cells collected from 18 patients with LP and 22 healthy control subjects were stimulated with agonists of TLR4, TLR7, TLR7/TLR8 or TLR9. Frequencies of circulating IFN-α+ plasmacytoid DCs (pDCs); TNF-α+ myeloid DCs (mDCs); regulatory T cells (Tregs); and IL-17-, IL-10-, IL-22-, TNF-, and IFN-γ-secreting T cells were assessed via flow cytometry. Results The frequencies of regulatory CD4+ and CD8+ CD25+ Foxp3+ CD127low/− T cells and TNF-α+ mDCs were induced following activation with TLR4, TLR7 and TLR8 agonists in the LP group. Moreover, increased baseline frequencies of CD4+ IL-10+ T cells and CD8+ IL-22+ or IFN-γ+ T cells were found. In the LP group, TLR4 activation induced an increased frequency of CD4+ IFN-γ+ T cells, while TLR7/8 and staphylococcal enterotoxin B (SEB) activation induced an increased frequency of CD8+ IL-22+ T cells. An increased frequency of polyfunctional CD4+ T cells that simultaneously secreted 3 of the evaluated cytokines (not including IL-10) was verified upon TLR7/8/9 activation, while polyfunctional CD8+ T cells were already detectable at baseline. Conclusions TLR-mediated activation of the innate immune response induced the production of proinflammatory mDCs, Tregs and polyfunctional T cells in patients with LP. Therefore, TLR activation has an adjuvant role in inducing both innate and adaptive immune responses.